Predictive value of Type D personality for impaired endothelial function in patients with coronary artery disease. (15th May 2018) - Denollet, Johan; van Felius, Romy A.; Lodder, Paul; Mommersteeg, Paula M.; Goovaerts, Inge; Possemiers, Nadine; Vanhees, Luc; Beckers, Paul; Pattyn, Nele; Van Craenenbroeck, Emeline M.
Abstract: Background: Type D personality (high negative affectivity and social inhibition) is associated with cardiovascular events and coronary plaque severity. Whether Type D is also related to functional vasomotion abnormalities is unknown. We examined concurrent and predictive associations of Type D with endothelial dysfunction in patients with coronary artery disease (CAD). Methods: At baseline, 180 CAD patients (90% men; M = 58.0 years) completed Type D (DS14) and depression scales, and entered a 12-week exercise program. Flow-mediated dilation (FMD) of the brachial artery and circulating CD34 + /KDR + /CD45 + dim endothelial progenitor cells (EPCs) were assessed at baseline, 3 months, and 12 months. Logistic regression and linear mixed models were used to analyze endothelial function. Results: Type D personality was associated with decreased FMD across baseline, 3 months, and 12 months (mixed model analysis, p = 0.04), after adjustment for clinical characteristics, exercise training and depression. There was no significant association between Type D and decreased EPCs (p = 0.07). Age and smoking were other significant correlates of FMD and EPCs. Using a FMD <5.5% cut-off, Type D patients more often had endothelial dysfunction at baseline (24/37 = 65%) than non-Type Ds (63/143 = 44%); OR = 3.03, 95% CI 1.04–8.80. This significant Type D effect was confirmed in prospective analyses of endothelial dysfunction at 12 months (OR = 3.43, 95% CI 1.01–11.64), and in subgroup analyses of male patients. Conclusions: Type D personality was associated with impaired endothelial function in men with CAD. This association was robust across time, independent from depressive symptoms, and supports the notion that Type D has an adverse effect on cardiovascular health in patients with CAD. Highlights: Type D personality was associated with decreased flow-mediated dilation (FMD) of the brachial artery in patients with CAD. This association was robust across time (baseline, 3 months, and 12 months) and independent from age and depression. Type D patients had an increased risk of endothelial dysfunction (FMD < 5.5%). Type D personality has an adverse effect on cardiovascular health in patients with CAD.